مشكلات تعليم التفكير من وجهة نظر معلمي ومديري مدارس الحلقة الأولى من التعليم الأساسي في محافظة اللاذقية - سليمان جمال; العاتكي سندس (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى تحديد مشكلات تعليم التفكير المتعلقة بكل من المحاور الستة (البيئة الصفية، محتوى المناهج الدراسية، المعلم، البيئة المدرسية، التقنيات التعليمية، التقويم) من وجهة نظر عينة من معلمي ومديري مدارس الحلقة الأولى من التعليم الأساسي بلغ عددهم (125) معلماً ومعلمة و(45) مديراً ومديرة. تم استخدام استبانة تضمنت مشكلات تعليم التفكير في كل من المحاور السابقة الذكر، وقد توصل البحث إلى تحديد مجموعة من المشكلات منها: لجوء المعلم إلى الأوامر والتعليمات في التعامل مع التلاميذ، ضعف تأهيل المعلم وتدريبه، عدم اهتمام إدارة المدرسة بتوفير دليل يرشد المعلم إلى كيفية تعليم التفكير، عدم توظيف التقنيات الحديثة في النشاطات التعليمية، تناسب أساليب التقويم مع الطرائق التي تركز على الحفظ والاستظهار. كما تم إثبات وجود فروق دالة إحصائياً في وجهة نظر كل من المعلمين والمديرين في مشكلات تعليم التفكير تعزى لمتغير المؤهل العلمي أو التربوي. This research aims at defining the problems of the six aspects (classroom environment, the content of academic curriculum, the teacher, school environment, teaching aids, and evaluation). This will be done on the basis of a sample of teachers and principals in the first stage of Basic Education. The number of male and female teachers is (125) and the number of principals is (45) males and females. A questionnaire, which included the problems of teaching thinking in the aspects mentioned above, was used. The research concluded the definition of a set of problems, including the following: the teacher’s usage of commands and instructions in dealing with hisstudents, the curriculum is crowded, the weakness of the teacher’s qualification and training, the carelessness of school’s administration, in respect of providing a guide book, which can help the teacher teach thinking, not using the new technologies in teaching activities and the suitability of evaluation ways with the methods that are based on memorizing and reciting. Statistical significant differences also exist in principals’ points of view on one hand and the teachers’ on the other hand, with regard to teaching thinking, in accordance to the educational and academic level.